Different mouse mast cell populations express various combinations of at least six distinct mast cell serine proteases. - Reynolds, D S (1990)
Mouse serosal mast cells (SMCs) and Kirsten sarcoma virus-immortalized mast cells store large amounts of mast cell carboxypeptidase A and serine proteases in their secretory granules. Secretory granule proteins from 2.6 x 10(6) purified SMCs were separated by NaDodSO4/PAGE, trans-blotted to poly(vinylidine difluoride) membranes, and subjected to amino-terminal amino acid sequencing. Four distinct mast cell serine proteases were identified. With mast cell carboxypeptidase A, these serine proteases comprise the major proteins of mouse SMC secretory granules. Each of the four SMC serine proteases was distinct from the two serine proteases present in mucosal mast cells in the intestines of helminth-infected mice. The secretory granules of a Kirsten sarcoma virus-immortalized mast cell line contained three of the SMC-derived serine proteases and one of the mucosal mast cell-derived serine proteases. Thus, the family of mouse mast cell secretory granule serine proteases has at least six distinct members that can be expressed in different combinations in different mast cell populations.